Perancangan Prototype Pemberi Pakan Kucing Otomatis Berdasarkan Umur Berbasis Sms Gateway - Bayu Jaka Valendio; Susilawati Susilawati; Zulfikar Sembiring (Jurnal Ilmiah Teknik Informatika & Elektro (JITEK), 2022)
Of the several animals that we know, the cat is one of the most popular pets in today's society. However, in order to keep the pet cat in good health, cat keeper must pay more attention to the food schedule otherwise the cat will be susceptible to disease, so it can harm the cat itself. In today's modern era, many things can be designed to make activities easier. One of them is the design of a prototype automatic cat feeder. The purpose of this research is to design and make an automatic cat feeding device using Arduino Uno R3 as the brain in this series which then uses Arduino IDE software and C++ programming discussion to input the data that will be needed. Furthermore, this tool will also be directly connected to the RTC (Real Time Clock) as a benchmark for the hour and date and the servo motor as a valve controller, so that the feeder will open according to the input schedule. This tool also uses the GPRS Shield 800L as a sender of SMS notifications when the prediction feed is running out. Finally, this one set of tools also uses a step down module which can be used as a voltage adjustment for the feeder. This tool can later be useful, especially for cat shelter owners/keepers because it can provide feed according to a time and schedule whose own dose can be inputted based on age. The advantage of this tool is that it can last for approximately 2 hours without electricity (possibly when the power goes out) specifically for sending notifications.